Development of anti-inflammatory soap enhnaced by green coffee bean oils / Muhammad Afiq Ramli - Ramli, Muhammad Afiq (2019)
Green coffee contains a large quantity and variety of polyphenols and fiavonoids. The composition of the polyphenols in coffee, due to the formation of compounds generated by Maillard reaction, which can have anti-inflammatory potential. Inflammatory skin illnesses are the most well-known issue in dermatology. This type of illness has been known one of the biggest illness in Malaysia for the past few years. Thus, in this study shows the reliable on Green Coffee Bean oils extracted using Soxhlet extraction to be applied in commercial soap for the anti-inflammatory effect. A simple method for the determination of chlorogenic acids content in green coffee bean was reported. The method was based on the use of UV/Vis absorption. It is relevant that the quantification of and chlorogenic acids was performed without their preliminary chemical separation despite their spectral overlap in the range 200-400 nm. Themolar extinction coefficients chlorogenic acid in ethanol solution was calculated by using the chemical standards; the estimated values were £(272nm) = 12159 ± 97M-1 cm-1 for chlorogenic acids molecules. The anti-inflammatory effects extracts of GCB applied in soap was investigated in animal models and using a DPPH radical scavenging test. In the formalin test the extracts reduced licking activity.